Criminals Work from Home during Pandemics Too: a Public Health Approach to Respond to Fraud and Crimes against those 50 and above - Payne, Brian K. (American journal of criminal justice, 2020)
This paper uses the public health framework to address the apparent impact of the coronavirus on the victimization experiences with a specific focus given to those over the age of 50. The bulk of attention is given to fraud victimization, with consideration also given to parent abuse, partner violence, and patient abuse. A review of data from the Federal Trade Commission shows that reports of most types of fraud grew significantly in the first three months of 2020 in comparison to the same time period in 2019. Differences between fraud experiences based on age are considered. Older persons lost much more to fraud than younger persons, and far more in 2020 than 2019. In addition, they reported being targeted more often for certain types of cybercrime (i.e., tech support scams). While devastating to everyone, it is concluded that the coronavirus will potentially have a more significant impact on the financial health of older persons than younger persons. It is concluded that minimizing the consequences of all forms of crimes targeting older adults will be best achieved by using a public health approach.